UNDERSTANDING THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND PERCEIVED ENJOYMENT ON ATTITUDE AND BUYING INTENTION USING BUY NOW PAY LATER SERVICE - Aqilla Abdurrahman Jundiy; Erlita Ridanasti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the factors that influence consumer attitudes and buying intentions toward Buy Now, Pay Later (BNPL) services in Indonesia, using the Technology Acceptance Model (TAM) as a framework. It focuses on three key factors: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Perceived Enjoyment (PE), and how these affect attitudes toward BNPL services and, in turn, influence buying intentions. Data was collected from 200 respondents via an online survey, and the results were analyzed using Structural Equation Modeling (SEM). The findings show that PU, PEOU, and PE significantly impact consumer attitudes, with PU having the strongest influence. Positive attitudes lead to greater intention to use BNPL services. This study provides valuable insights for BNPL providers, highlighting the need to enhance ease of use, usefulness, and enjoyment to increase user adoption. Recommendations for improving marketing strategies and user interfaces are also discussed, along with implications for policymakers to ensure responsible use of BNPL services.